NILAI SOSIAL DALAM NOVEL HADIAH TERAKHIR KARYA RAHMALITA - Rodiah Nitami; Syafrial Syafrial; M. Nur Mustafa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the aim of analyzing the social values contained in the novel Last Gift by Rahmalita. The method used in this research is qualitative research. Data collection techniques in this study are text analysis techniques. Data analysis techniques carried out in this study are grouping research data, describing research results, interpreting research results, based on these descriptions, it can be concluded that in this study found social values obtained from novels The Last Prize of Rahmalita's work consists of six categories, namely: social value, caring category, 21 values, social value, togetherness category, 5 values, social value, cooperation category, 1 value, social value, helping category, 8 values, social value, friendship category as much as 4 values and social values remind good things as much as 2 values.Key Words: Value, Social Value, Final Gift Novel